Characteristics of Structures in the Poem "Nam Al-Khali" By the poet Al-Aswad Bin Yafur: Descriptive Semantic Study - Alabdooli, Moaza; Bialeajid, Maryam (Al-Adab Journal, 2024)
The research deals with the grammatical structures in the poem "Nam Al-Khali" by the pre-Islamic poet Al-Aswad Bin Yafar. It is a poem in which he laments himself and anticipates his death after his old age and blindness. The research aims to study grammatical structures and their relationship with the anxious and melancholy psychology of the poet, and how it affected the composition of meaning. The research began with a preface that defines the structure and its divisions, and the relationship of the structure to semantics, then the poem studied. The research contains four axes, the first: the structures of news, the second: the structures of construction, the third: presenting what is due for delay, and the fourth: other structural characteristics. The study relied on the descriptive and analytical approach. The results of the study showed that the poem is characterized by a variety of grammatical structures that have close connotations with the meanings of self-pity and its bleak present. The past tense phrasal verbs dominated the poem, and the nominative sentences came in the adjectives and mentioned places to indicate stability and stability.